SOSIALIASI LITERASI DIGITAL FINANCE PADA ACARA WEBINAR GORESAN PENA WANITA VOLUME SEMBILAN: Socialization of Digital Finance Literacy at the Webinar Event of Goresan Pena Wanita Volume Nine - Muhamad Rahmat; Maya Richmayati; Elminaliya Sandra; Nur Isra Laili; Sarmini Sarmini (ASOSIASI IDEBAHASA KEPRI, 2023)
E-commerce and Financial technology make it easy. Digitalization activity No only machine progress economy but also a factor most importantly starting change positively. Fintech payments must Keep going innovative Because high benefits and convenience _ For make difference implementation management of Indonesian state finances. Startups are divided two type namely e-commerce and financial technology (FinTech). Online Shop is a company give selling platform facilities to buy online, FinTech focuses on companies that use modern technology for innovate in the field service finance. Online shopping and FinTech work in a manner synergistic One each other, where online shopping provides a platform for sell buy, meanwhile FinTech presence supports the selling process buy so that can be accepted by society broad. financial technology in the current era This must become part from life No something to be avoided Because the benefits Lots once and a weakness too of course there, of activity This expected result open horizon society and student’s importance follow technology. FinTech is useful for society, country and players. For consumer the benefits are get more service _ well, more choice _ a lot and the price is more cheap. FinTech is also useful for player i.e. simplify _ chain transaction, pressing cost operational and capital costs, and freeze channel information. Whereas for the country the benefits of fintech are push transmission policy economy, increase speed money circulation so increase economy society and drive the national strategy finance.